PERANCANGAN BASIS DATA SISTEM INFORMASI PERWIRA TUGAS BELAJAR (SIPATUBEL) PADA KEMENTERIAN PERTAHANAN - Alvin Dwi Hardiansyah (2020)
Perwira Tugas Belajar Information System (SIPATUBEL) is an information system that is useful for recording all data that covers the education of Ministry of Defense employees such as employees who receive scholarships, employees who are on leave for study assignments, all of which are recorded in SIPATUBEL. The purpose of this research is to support the application of SIPATUBEL in the affairs of data collection using a database and help report data easily with the database system that the author is designing. The Design Method that author use is Database System Development Life Cycle (DSDLC), because this method can analyze, design and even develop a database system and this method is very suitable with the research that the author was made.